THE USE OF GUESSING GAME IN IMPROVING STUDENTS’ SPEAKING SKILL AT SMP NEGERI 3 TONDANO - Valincia Febry Lim Pinangkaan; Mister Gidion Maru; Yapi Henri Wongkar (SoCul: International Journal of Research in Social Cultural Issues, 2022)
The aim of this study was to determine whether or not employing a guessing game may improve students' speaking skills. The pre-experimental design was employed in this study, with one group pre-test-post-test. For data analysis, the researcher used statistical analysis by SPSS (Statistical Product and Service Solution) version 22 with Paired sample t-test. The Paired sample t-test results suggest that students speaking skills have significantly improved. The mean score of the pre-test before employing the guessing game in teaching is M = 37,78 with a standard deviation of 13.086. After the guessing game treatment, the mean post-test score is M = 60,00 with a standard deviation of 16.270. The total number of students (N) is 18. The study discovered that using a guessing game in the classroom might improve students' speaking skills. It demonstrates that the study hypothesis (H1) is accepted and the null hypothesis (H0) is rejected, or that the outcome has addressed the research question that the guessing game may considerably enhance students' speaking skills. As a result, the guessing game can help students improve their speaking skills.